Unraveling complexity and leveraging opportunities in uncommon breast cancer subtypes - Fresia Pareja; Rohit Bhargava; Virginia F. Borges; Edi Brogi; Rita Canas Marques; Fatima Cardoso; Christine Desmedt; Malini Harigopal; Sunil R. Lakhani; Adrian Lee; Jose Pablo Leone; Hannah Linden; et al. (npj Breast Cancer)
Abstract Special histologic subtypes of breast cancer (BC) exhibit unique phenotypes and molecular profiles with diagnostic and therapeutic implications, often differing in behavior and clinical trajectory from common BC forms. Novel methodologies, such as artificial intelligence may improve classification. Genetic predisposition plays roles in a subset of cases. Uncommon BC presentations like male, inflammatory and pregnancy-related BC pose challenges. Emerging therapeutic strategies targeting genetic alterations or immune microenvironment are being explored.